2007
DOI: 10.1086/518892
|View full text |Cite
|
Sign up to set email alerts
|

Association of ICAM3 Genetic Variant with Severe Acute Respiratory Syndrome

Abstract: Genetic polymorphisms have been demonstrated to be associated with vulnerability to human infection. ICAM3, an intercellular adhesion molecule important for T cell activation, and FCER2 (CD23), an immune response gene, both located on chromosome 19p13.3, were investigated for host genetic susceptibility and association with clinical outcome. A case-control study based on 817 patients with confirmed severe acute respiratory syndrome (SARS), 307 health care worker control subjects, 290 outpatient control subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…More recently, Chan et al re-examined additional non-synonymous coding SNPs of FCER2 and one SNP in ICAM3 28. Their data were consistent with our findings in that there was no association between the SNPs in FCER2 and SARS.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, Chan et al re-examined additional non-synonymous coding SNPs of FCER2 and one SNP in ICAM3 28. Their data were consistent with our findings in that there was no association between the SNPs in FCER2 and SARS.…”
Section: Discussionsupporting
confidence: 91%
“…The study was approved by the Clinical Research Ethics Committee of the Institute Review Board of the University of Hong Kong/Hospital Authority Hong Kong West Cluster. The SARS patients were recruited as described previously [27]. Further recruitment of additional serologically confirmed SARS patients increased the total number of cases for this study to 824.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Binding of ICAM3 to CD209 is mediated at domain 2 of the soluble ICAM3 [35]. Our previous association study for SARS-CoV infection showed that the ICAM3 Asp143Gly SNP (ϩ443AϾG; dbSNP: rs2304237) demonstrated significant association with higher LDH levels and lower total white blood cell counts on admission [27]. Replacement of a charged aspartate by a neutral glycine of this ICAM3 SNP may affect exposure of an N-linked glycosylation site, possibly affecting interaction between ICAM3 and CD209.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations